Case Report: Anti-interferon-γ autoantibodies in an adolescent with disseminated Talaromyces marneffei and mycobacterial co-infections - Bingkun Li; Bingkun Li; Tiantian Li; Tiantian Li; Qihua Huang; Qihua Huang; Nanfang Mo; Nanfang Mo; Xiaojuan He; Xiaojuan He; Zhiwen Jiang; Zhiwen Jiang; et al. (Frontiers in Pediatrics)
BackgroundAnti-interferon-γ autoantibodies (AIGAs) are associated with adult-onset immunodeficiency syndrome, which makes individuals susceptible to intracellular pathogen infections. However, AIGAs are rarely reported in adolescents.Case presentationWe report a 13-year-old Chinese boy who presented with fever, cough, and enlarged cervical lymph nodes. Blood cultures yielded Mycobacterium abscessus, and Talaromyces marneffei (TM) was cultured from pericardial effusion. Whole exome sequencing revealed no pathogenic variants. Notably, high levels of neutralizing AIGAs were detected in the patient's serum. After receiving treatment for Mycobacterium abscessus and antifungal therapy for TM, the patient showed significant improvement. However, at the 19-month follow-up, the patient developed a Mycobacterium asiaticum infection.ConclusionThis case highlights the importance of screening for AIGAs in pediatric patients with disseminated TM or NTM infections. Prolonged treatment and continuous follow-up remains crucial for managing pediatric patients with AIGAs.